2018
DOI: 10.1038/s41598-017-19024-z
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-free generation of uniform adipose spheroids for metabolism research and drug discovery

Abstract: Adipose tissue dysfunction is critical to the development of type II diabetes and other metabolic diseases. While monolayer cell culture has been useful for studying fat biology, 2D culture often does not reflect the complexity of fat tissue. Animal models are also problematic in that they are expensive, time consuming, and may not completely recapitulate human biology because of species variation. To address these problems, we have developed a scaffold-free method to generate 3D adipose spheroids from primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
127
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(137 citation statements)
references
References 52 publications
6
127
3
1
Order By: Relevance
“…In addition, Yang et al reported that murine adipose derived stromal cells were successfully differentiated into mature adipocytes with BAT pheno-type and function within 3D hydrogels [50]. For WA, 3D culture has been demonstrated to promote adipogenesis and adipokine secretion compared to 2D culture [51,52]. It has also been demonstrated that a porous structure could improve the cell viability in vitro and promote cell ingrowth and integration in vivo [35,53].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yang et al reported that murine adipose derived stromal cells were successfully differentiated into mature adipocytes with BAT pheno-type and function within 3D hydrogels [50]. For WA, 3D culture has been demonstrated to promote adipogenesis and adipokine secretion compared to 2D culture [51,52]. It has also been demonstrated that a porous structure could improve the cell viability in vitro and promote cell ingrowth and integration in vivo [35,53].…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of these cultures allowed lipid accumulation and these cultures secreted leptin, the archetypal adipokine. Other groups used adipose progenitors derived from the stromal-vascular fraction of human white adipose tissue and self-organised them into spheroids in hanging drops [81] or by first stirring and then embedding them in Matrigel they generated self-organised vascularised organoids [82]. These novel protocols open the door to using long-term patient-derived adipose cultures to explore the pathology of adipose tissue in metabolic disease.…”
Section: Don't Believe the Hype: Organoid Limitationsmentioning
confidence: 99%
“…Adipose : Due to its central metabolic role in the regulation of energy homeostasis, adipose tissue is gaining more and more interest as an in vitro model in the context of metabolic disorders . Spheroid models, capable of accumulating and releasing fatty acids, have been formed with established cell lines and primary adipose‐derived stem cells …”
Section: Transferable In Vitro Organ Modelsmentioning
confidence: 99%